Implementation of new technologies in accounting and financial processes: An effectiveness assessment - Szmajser, Rafał; Kędzior, Marcin; Andrzejewski, Mariusz; Świetla, Katarzyna (International Entrepreneurship Review, 2022)
Objective: The aim of this paper is to explore accountants’ views on the usage of Robotic Process Automation technology (RPA) which brings efficiency increase. Research Design & Methods: An online survey has been addressed to over 500 respondents from international companies, where 160+ complete answers were received from the most important types of organizations in the business services industry. The non-parametric rho Spearman correlation coefficient and the non-parametric Kruskal-Wallis test and business case for the RPA implementation efficiency were used. Findings: Based on the research results obtained, it should be emphasized that robotization technologies which raise the efficiency of financial and accounting services make an important impact on the efficiency of modern business services sector. Application of RPA assumes replacing work of an existing employee with the use of dedicated software (software robots) to support activities, primarily repeated and uncomplicated, characterized by a low number of exceptions. Implications & Recommendations: RPA application is commonly used in modern business services, particularly in the areas of Finance, Accounting, IT and Human Resources Management. By utilizing RPA technology, the effectiveness of operations increases while reducing workload, minimizing possible errors in the process. The greatest efficiency resulting from the RPA implementation was observed in the Accounts Payable department, to a lesser extent in the General Ledger department and in the Tax section. The assessment of managers in terms of the effects of RPA implementation is unequal, while for Business, IT Process Outsourcing companies (BPO / ITO), Shared Service Centers (SSC), Consulting / Advisory companies and their customers no significant differences were found. Contribution & Value Added: The article presents an assessment of the effectiveness of the use of Robotic Process Automation in Process Outsourcing companies (BPO / ITO) and Shared Service Centers (SSC) operating in Poland. It is one of the first studies of this type for enterprises operating in Poland. The article uses a relatively large number of responses (160+) from the respondents. In the previous studies in the literature, the answers obtained came from a much smaller number of respondents and were conducted in the form of direct interviews. In the article, the group of respondents consists not only of managers of outsourcing companies, but also auditing companies and clients of outsourcing companies. The article also presents a financial simulation of the effectiveness of BPO / ITO and SSC using Robotic Process Automation, which additionally validates the responses obtained in the questionnaire.